2018
DOI: 10.1093/infdis/jiy027
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Effectiveness Against Influenza A(H3N2) Hospitalizations in Children in Hong Kong in a Prolonged Season, 2016/2017

Abstract: Influenza vaccination was effective in preventing hospitalizations in children in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This pattern was observed in other countries in the region, with a record number of infections notified in Australia, and an unusually prolonged season in Hong Kong. 27,28 Similar findings have also been reported from the Northern hemisphere 2017/18 winter. 29 These seasons have been dominated by A/H3N2 and estimates of vaccine effectiveness against this subtype have been low.…”
Section: Discussionsupporting
confidence: 75%
“…This pattern was observed in other countries in the region, with a record number of infections notified in Australia, and an unusually prolonged season in Hong Kong. 27,28 Similar findings have also been reported from the Northern hemisphere 2017/18 winter. 29 These seasons have been dominated by A/H3N2 and estimates of vaccine effectiveness against this subtype have been low.…”
Section: Discussionsupporting
confidence: 75%
“…We analysed data from a test-negative study designed to monitor influenza VE against hospitalization in children in Hong Kong across 5 years from 1 September 2012 through 31 August 2017. 1619 Children between 6 months and 17 years of age were included in the analysis if they were admitted to general wards in four public hospitals in Hong Kong with fever ≥38°C and any respiratory symptom such as runny nose, cough or sore throat. As previously described, 1619 nasopharyngeal aspirates were collected from all eligible children and initially tested by direct immunofluorescence assay and then subsequently tested by culture and reverse transcription polymerase chain reaction (RT-PCR).…”
Section: Methodsmentioning
confidence: 99%
“…In this established study, we previously reported influenza VE against hospitalization in children in 2009–2013, 16 in 2009–2014 for influenza B viruses, 17 in 2015/16, 18 and in 2016/17. 19 Here, we analysed data from five consecutive years to assess how influenza VE changes by time intervals between vaccination and hospitalization, taking advantage of almost year-round circulation of influenza in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…We enrolled children who were admitted with a febrile acute respiratory illness (ARI) to the general paediatric wards in these three hospitals. Febrile ARI was defined as fever measured ≥ 38 °C plus any respiratory symptom such as cough, sore throat or runny nose [3-5]. Healthcare staff collected nasopharyngeal aspirates from all enrolled children and tested for influenza viruses by reverse transcriptase PCR.…”
Section: Study Participantsmentioning
confidence: 99%
“…Previous influenza A(H1N1)pdm09 epidemics occurred in 2012/13, 2013/14 and 2015/16 [3,4]. Here we continued an ongoing study [3-5] using the test-negative design [6,7] to estimate influenza vaccine effectiveness (VE) in hospitalised children in Hong Kong in the early part of the 2018/19 winter influenza season.…”
mentioning
confidence: 99%